1997
DOI: 10.1677/joe.0.1530049
|View full text |Cite
|
Sign up to set email alerts
|

Two oxytocin-binding site subtypes in rat kidney: pharmacological characterization, ontogeny and localization by in vitro and in vivo autoradiography

Abstract: The localization of oxytocin (OT)-binding sites in the developing rat kidney and their pharmacological characterization were investigated by means of autoradiographic techniques. The cellular localization was studied by application of the histoautoradiographic technique to (1) frozen sections and semithin sections from kidney slices incubated in vitro in the presence of a 125I-labelled OT antagonist and (2) frozen and semithin sections from kidneys after in vivo systemic infusion of the radioligand. Pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The endogenous plasma concentrations of oxytocin in our anaesthetized rats were within the range achieved by doses of oxytocin previously shown to increase GFR (Forsling et al 1994, Windle et al 1997. Receptors for oxytocin have been located in the glomerulus (Stoeckel et al 1987) and the macula densa region of the tubule (Stoeckel & Freund-Mercier 1989, Arpin-Bott et al 1997, and it seems reasonable to propose that these might have mediated the observed change in GFR (the macula densa being intimately involved in the tubulo-glomerular feedback control of GFR; Briggs & Schnermann 1987).…”
Section: Resultssupporting
confidence: 66%
“…The endogenous plasma concentrations of oxytocin in our anaesthetized rats were within the range achieved by doses of oxytocin previously shown to increase GFR (Forsling et al 1994, Windle et al 1997. Receptors for oxytocin have been located in the glomerulus (Stoeckel et al 1987) and the macula densa region of the tubule (Stoeckel & Freund-Mercier 1989, Arpin-Bott et al 1997, and it seems reasonable to propose that these might have mediated the observed change in GFR (the macula densa being intimately involved in the tubulo-glomerular feedback control of GFR; Briggs & Schnermann 1987).…”
Section: Resultssupporting
confidence: 66%
“…11 In contrast, the contractile effect of OT on cultured myometrium cells was blocked by an OT receptor, but not V1 receptor, antagonist. 11 OT receptors have been identified in the kidney, 12 and OT has been shown to exert an antidiuretic effect in vasopressin-deficient Brattleboro rats 9,10 and to increase water transport in isolated IMCD. 8,9 These effects have been shown to be abolished by the administration of a V2 vasopressin receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work the oxytocin antagonist chosen appeared to have no such partial agonist effect, as indicated by stimulated cAMP production. It has been suggested that there could be two subtypes of oxytocin receptors in the kidney (Arpin-Bott et al 1997), and in the uterus, where GN-OVT inhibited both the uterotonic action and prostaglandin-releasing action of oxytocin, whereas [Pen',pMePheZ ,Thr4,0rns]oxytocin only inhibited the uterotonic action of oxytocin (Chan el al. 1993).…”
Section: Discussionmentioning
confidence: 99%